COVID-19 and Canadian Gastroenterology Trainees. Issue 3 (24th October 2020) - Khan, Rishad; Tandon, Parul; Scaffidi, Michael A; Bishay, Kirles; Pawlak, Katarzyna M; Kral, Jan; Amin, Sunil; Bilal, Mohammad; Lui, Rashid N; Sandhu, Dalbir S; Hashim, Almoutaz; Bollipo, Steven; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has impacted endoscopy services and education worldwide. This study aimed to characterize the impact of COVID-19 on gastroenterology trainees in Canada. Methods: An analysis of Canadian respondents from the international EndoTrain survey, open from April 11 to May 2 2020 and distributed by program directors, trainees, and national and international gastroenterology societies' representatives, was completed. The survey included questions on monthly endoscopy volume, personal protective equipment availability, trainee well-being and educational resources. The primary outcome was change in procedural volume during the COVID-19 pandemic. Secondary outcomes included trainee's professional and personal concerns, anxiety and burnout. Results: Thirty-four Canadian trainees completed the survey. Per month, participants completed a median of 30 esophagogastroduodenoscopies (interquartile range 16 to 50) prior to the pandemic compared to 2 (0 to 10) during the pandemic, 20 (8 to 30) compared to 2 (0 to 5) colonoscopies and 3 (1 to 10) compared to 0 (0 to 3) upper gastrointestinal bleeding procedures. There was a significant decrease in procedural volumes between the pre-COVID-19 and COVID-19 time periods for all procedures ( P < 0.001). Thirty (88%) trainees were concerned about personal COVID-19 exposure, 32 (94%) were concerned about achieving and/or maintaining clinical competence and 24 (71%) were concerned about prolongation of training time due to the pandemic. Twenty-six (79%) respondents experienced some degree of anxiety, and 10 (31%) experienced some degree of burnout. Conclusion: The COVID-19 pandemic has substantially impacted gastroenterology trainees in Canada. As the pandemic eases, it important for gastrointestinal programs to adapt to maximize resident learning, maintain effective clinical care and ensure development of endoscopic competence.